A Case of Trisomy 9. Issue 2 (June 1973) - Feingold, Murray; Atkins, Leonard
Abstract : The first patient with trisomy 9, an infant who survived 28 days, is reported. Clinical findings included microcephaly, low-set malformed ears, small palpebral fissures, enophthalmos, bulbous nose, micrognathia, low hairline, congenital heart disease, skeletal abnormalities, small penis, hypoplastic scrotum, and a Dandy-Walker like deformity of the fourth ventricle.